What is consciousness and what it is for. An introduction to extended information theory - Forti, Bruno (Frontiers in Psychology, 2025)
In this paper, I outline a new theory on consciousness, the Extended Information Theory. This theory jointly addresses issues related to the nature of consciousness and those related to its functional role. The phenomenal analysis of the simplest aspects of experience allows us to identify the structure of consciousness within consciousness itself. The simplest forms of experience are not found in sensations, but in forms of perception in which the qualitative aspects of consciousness necessarily have relational significance. Furthermore, this analysis leads us to hypothesize that the structure of an early visual experience is constituted by a Hierarchy of Spatial Belongings nested within each other. This structure makes it possible to identify a property of consciousness that is more fundamental than qualitative aspects. It can be identified in the fact that a conscious content, like an object, extends in a certain way into the space to which it belongs. Even when faced with an unfamiliar image, this allows us to know how its contents extend into the space to which they belong. The primary role of consciousness could thus be identified in knowing, in the immediacy of experience, the structural aspects of the physical world that surrounds us. From a functional point of view, it can be stated that consciousness handles Extended Information and differs from Non-Conscious systems that handle point-like information. It is in this characteristic, which enables it to overcome some of the limitations of computation, that the evolutionary meaning of consciousness may lie. The phenomenal analysis of early perception allows us to examine this process of knowledge and to propose a tentative hypothesis regarding its functioning. Finally, the paper discusses the difference between the EIT, which reflects the need to integrate information about the structure of the stimulus, and theories based on classical integration.